The Role of Sports, Peer Support, and Teacher Involvement in Bullying: A Quantitative Study from the Teachers’ Perspective - Muzakki, Abdurrohman; Nuryady, Mirza; ‘Allaamsyah, M. ‘Ainurridho (Jurnal Pendidikan Progresif, 2025)
The Role of Sports, Peer Support, and Teacher Involvement in Bullying: A Quantitative Study from the Teachers’ Perspective. Objectives: The research aims to analyze teachers' perceptions of the direct effects of sports activities, colleagues' support, and their role in bullying behavior; to explore the mediating role of mental health; and to examine the moderating effect of self-regulation from the teachers' perspective. Methods: A quantitative method involving Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed. The sample consisted of 250 sixth-grade elementary school teachers in the Rampah District. The data were collected using a 5-point Likert scale structured questionnaire that assessed teachers' perceptions of student bullying behavior, mental health, peer support, and self-regulation. The data were then processed to evaluate the measurement model and the structural model. Findings: This study revealed that teachers regarded sports activities and their role as the primary direct factors influencing the reduction of bullying. The study results indicated that the proposed direct influence of peer support on bullying (H2) was not confirmed (β = -0,021, p = 0,312). Rather, the teachers viewed peer support as a significant indirect influence, leading to a notable improvement in students' mental health (β = 0.494, p < 0.001), which in turn contributed to a decrease in bullying behavior. The teachers' perceptions suggested that mental health was a significant mediator in the relationship between the protective school factors and bullying behavior. Moreover, according to teachers' assessments, self-regulation had a moderating effect and was instrumental in elevating the impact of mental health on bullying abatement. The model accounts for 37.7% of the variance in teachers' perceptions of mental health and 50.8% of the variance in bullying behavior, with a predictive relevance (Q²) of 0.694, indicating strong explanatory power. Conclusion: The findings confirm that preventing bullying in schools requires a comprehensive strategy that incorporates physical activities, peer relationships, teacher participation, and mental health promotion, facilitated by self-regulation training. This research contributes to the current conceptual models of bullying prevention from the perspective of teachers, providing practical advice for creating a safer and more supportive educational setting grounded in educators' viewpoints. Keywords: bullying, sports activities, peer support, teacher’s role, mental health, self-regulation.